2020
DOI: 10.3390/ijerph17114033
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome of Children Living in an Isolated Area in Myanmar

Abstract: Several studies have shown that the oral microbiome is related to systemic health, and a co-relation with several specific diseases has been suggested. The oral microbiome depends on environmental- and community-level factors. In this observational study, the oral microbiomes of children of isolated mountain people were analyzed with respect to the core oral microbiome and etiology of dental caries. We collected samples of supragingival plaque from children (age 9–13) living in the Chin state of Myanmar. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The prevalence pattern of dental caries varies with age and sex [ 16 , 17 , 18 , 19 , 20 ]. It depends on race, geographical location, socioeconomic status, nutrition habits, oral hygiene practices, and oral microbiome [ 21 , 22 , 23 , 24 ]. There are twenty teeth in the primary dentition.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence pattern of dental caries varies with age and sex [ 16 , 17 , 18 , 19 , 20 ]. It depends on race, geographical location, socioeconomic status, nutrition habits, oral hygiene practices, and oral microbiome [ 21 , 22 , 23 , 24 ]. There are twenty teeth in the primary dentition.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the difference in oral microbiome in people living in a different place had similarities to our findings in urban areas. A study in Myanmar with supragingival plate samples collected from children aged 9-13 years old living in remote mountains areas found that Proteobacteria (58.1%) account for the highest abundance, followed by Firmicutes (21.5%), and Bacteroidetes (14.8%) [23]. Jiang and colleagues reported similar findings, suggesting that children with abundant Proteobacteria (greater than 50%) and Actinobacteria (greater than 25%) developed fewer caries [24].…”
Section: Discussionmentioning
confidence: 88%
“…The data presented in this study were from Japanese older persons. Even though dietary habits have little effect on the oral microbiome [54], regional or cultural differences could have an effect on the oral microbiome [44]. The health status of the subjects who participated in this study was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) amplification was performed using primers specific to the V3-V4 region pyrosequencing tags of the 16S rRNA gene in the extracted bacterial DNA. Taxonomic classification of each read was assigned based on a search of the EzBioCloud 16S database [42,43], which contains the 16S rRNA genes of type strains that have valid published names and representative species-level phylotypes of both cultured and uncultured entries in the GenBank database, with complete hierarchical taxonomic classification from the phylum to species level [44].…”
Section: Microbial Community Analysismentioning
confidence: 99%